Camshaft design for a six-stroke engine - Mohd Nurunnajmi, Amat Janji (2012)
An internal combustion engine generally utilizes a conventional four stroke process including an intake stroke, compression stroke, expansion stroke, and exhaust stroke and in addition to this four stroke process, adds a secondary process having two additional strikes for scavenging process employs a fresh air intake stroke and a fresh air exhaust stroke to exhaust any remaining burnt and unburnt gases from the combustion chamber. A six-stroke internal combustion engine with reciprocating pistons wherein the six strokes are the admission of air, the first compression accompanied or followed by a possible cooling, a second compression followed by a combustion, the first expansion producing also a usable work and finally the discharge of the combustion gases, this engine, whose combustion is either with gasoline version or diesel version will included preferably a multiple of five non-uniform cylinders, and will have an energy efficiency of up to 30% higher than that of a four-stroke internal combustion. This study was focused to fabricate the six-stroke engine camshaft by using the variety machining such as conventional lathe machine, milling machine and EDM wire cut. This also limited to the modelling of the camshaft using computer aided design (CAD) and computer aided manufacturing (CAM). At the end of the study, there have results and discussions about camshaft problem and measured stress that exert to the camshaft. Result are taken from the different material which is mild steel (AISI 1080) and stainless steel (AISI 202). Data showed that stainless steel is greater than mild steel as a conclusion.